Supporting Preventative Medicine Decisions: An Extended Dual Processing Model that Incorporates a Cultural Worldviews Perspective - Scarffe, Andrew (Université d'Ottawa / University of Ottawa, 2024)
This thesis extends the dual processing model for decision threshold analysis to include the influence of an individual's risk perception as informed by their cultural worldviews. The Extended Dual Processing Model (DPM+) integrates cultural worldviews and risk perception into decision threshold analysis by way of an individual's 'type I system' reasoning. DPM+ offers a prescriptive explanation of how people of differing cultural worldviews may have different decision thresholds. DPM+ is contextualized for decision-making relative to preventative medicine. This thesis makes three important contributions: first, it presents a comprehensive scoping review of decision thresholds in medical decision making. Second, it theoretically extends the dual processing model to include risk perception as informed by a cultural worldviews dimension, forming the DPM+. Finally, the thesis demonstrates a proof-of-concept analysis of the practical application of DPM+, which demonstrates how DPM+ can prescriptively explain heterogeneity in decision thresholds according to cultural worldview.
Keywords: decision-making; risk perception; cultural worldviews; cultural cognition; regret; regret theory; dual processing model; preventative medicine; management; decision theory; decision threshold; decision analysis; decision threshold analysis; threshold analysis; standard of proof